Study On Concrete with Partially Replacement of Cement by Egg Sheel Powder and Steel Slag - Meshram, Himanshi; Nirmal, Pradeep Kumar; Singh, Lokesh (International Journal of Scientific Research in Civil Engineering, 2023)
In the present study an investigation the effect of partial replacement of cement by egg shell powder and steel slag on the various strength and durability properties of concrete by using the mix design of M30 grade of concrete .when cement production produces a large carbon dioxide and causes various effects in the atmosphere. In this program, the use of cement was used to reduce the waste of parts in common applications. It is made on properties of concrete by partial replacement of cement with egg shell and fine aggregate with steel slag. Egg shell powder concrete are varied up to 0 to 20% and steel slag is added to optimum egg shell powder content cement concrete from 0 to 20%.These two waste are recycled as an incomplete replacement of cement and fine aggregate and then characteristics compressive strength & split tensile strength after 7 and 28 days is analyzed and then it is compared with conventional normal concrete strength.
Keywords: Egg Shell; Compressive Strength; Spilit